2021
DOI: 10.1016/j.neo.2020.11.011
|View full text |Cite
|
Sign up to set email alerts
|

The forces driving cancer extracellular vesicle secretion

Abstract: The discovery that cancer cells discharge vast quantities of extracellular vesicles (EVs), underscored the explosion of the EV field. A large body of evidence now supports their onco-functionality in an array of contexts; stromal crosstalk, immune evasion, metastatic site priming, and drug resistance - justifying therapeutic intervention. The current bottleneck is a lack of clear understanding of why and how EV biogenesis ramps up in cancer cells, and hence where exactly avenues for intervention may reside. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 109 publications
1
35
0
Order By: Relevance
“…In addition, miR-1246 up-regulation in AP tissue samples did not reflect in AP plasma samples. Polyps tend to have lower ability of exosome production and thus of miR-1246 release into circulation, considering the adenomatous polyps as a precancerous condition [44,45]. Since our results were obtained from transcriptome and functional analyses in cancer tissues and cells lines, the oncogenic potential of miRNA-1246 should be further evaluated in a human organoid model derived from normal colon and adenomatous polyp tissues [46,47].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, miR-1246 up-regulation in AP tissue samples did not reflect in AP plasma samples. Polyps tend to have lower ability of exosome production and thus of miR-1246 release into circulation, considering the adenomatous polyps as a precancerous condition [44,45]. Since our results were obtained from transcriptome and functional analyses in cancer tissues and cells lines, the oncogenic potential of miRNA-1246 should be further evaluated in a human organoid model derived from normal colon and adenomatous polyp tissues [46,47].…”
Section: Discussionmentioning
confidence: 97%
“…To take full advantage of tEV, there is thus a need to better understand their kinetics during tumor development and therapy. Furthermore, there is a clear need to decipher why and how EV biogenesis ramps up in cancer cells, and what the specific avenues are for interventions (58). Here, we provide a much more granular insight into the composition and make-up of tEV in PDAC cell lines and in human plasma samples.…”
Section: Discussionmentioning
confidence: 97%
“…It should be emphasized, however, that studies have been reported showing that EVs from CSCs contribute significantly to tumor progression. Among the processes involved are tumor resistance, metastasis, angiogenesis, and maintenance of stemness and immune suppression [ 21 , 23 , 36 , 41 , 42 , 43 ]. The main role of EVs also includes their fusion with macrophages and other immune cells [ 30 , 31 ].…”
Section: Cscs and Their Evs Are Essential For Cancer Initiation And Its Processesmentioning
confidence: 99%